Manufacturing of IOT-Based Industrial Wastewater pH and TSS Monitoring Instruments Using RUT 955 - Supriyanto Suparno; Britantyo Wicaksono; Fatimah Nurul Qolbi (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2022)
According to data from the Environment Ministry of the Republic of Indonesia, 59 percent of Indonesian rivers are severely Polluted. The pollutant is due to many people's and industry's behavior of discharging waste directly into the river. This liquid waste contains solids and chemical compounds that affect river water's acidity (pH). Their pollutant does not meet the Government Regulation of the Republic of Indonesia Number 101/2014. Research has been carried out to manufacture an IoT-based sparing monitoring system device using RUT955 to measure the pH and TSS of industrial wastewater in remote areas. This sparring system uses two sources of electric current: PLN and the sun. Solar electricity stored in the battery is used to overcome the problem of breaking the electricity supply from PLN. The device made has been successfully connected to the internet using the webhook.site platform. Acquisition data storage is carried out using the google spreadsheet platform. The pH and TSS data measured by the sensor sent by RUT955 can be received and displayed on the internet platform. The measurement results that the sensor has carried out need to be calibrated so that the data sent is accurate.